2009
DOI: 10.1021/ac902009c
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Ion Mobility Spectrometry

Abstract: A novel method is proposed for enhancing the separation power of ion mobility spectrometry (IMS) and other similar pulsed techniques, such as time-of-flight mass spectrometry. In this technique, rather than generating an ion packet, a dip is created in the ion beam. This is achieved by an inverse pulse applied to the shutter grid. The dip moves with the same velocity as the ion packet, and the detector reads an inverse peak at the same drift time as that of the normal operation. Using this technique, we achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…The observed arrival curves resemble those in inverse ion mobility spectrometry where a continuous ion flux is disrupted by the gates, creating dips in ion intensity traces. 31 Importantly, the analyte-dependent appearance of 'dips' at +1375 V suggests differential ionization for the analytes. One possible explanation is the formation of multi-jets at higher voltages, 29 and a differential response of the jets to the field perturbation.…”
Section: Impact Of Spray Voltage On Perturbation-induced Pulsing Of Nano-esimentioning
confidence: 99%
“…The observed arrival curves resemble those in inverse ion mobility spectrometry where a continuous ion flux is disrupted by the gates, creating dips in ion intensity traces. 31 Importantly, the analyte-dependent appearance of 'dips' at +1375 V suggests differential ionization for the analytes. One possible explanation is the formation of multi-jets at higher voltages, 29 and a differential response of the jets to the field perturbation.…”
Section: Impact Of Spray Voltage On Perturbation-induced Pulsing Of Nano-esimentioning
confidence: 99%
“…The dip moved at the same velocity as the ion packet, and the detector read an inverse peak at a drift time similar to that of conventional linear mode of operation. This new technique, named inverse ion mobility spectrometry, was recently invented in our lab to enhance IMS resolution [30]. Except for the optimization, all the measurements including the calibration curve were obtained in the inverse mode.…”
Section: Ion Mobility Spectrometermentioning
confidence: 99%
“…The small OTA peak was surrounded by background peaks and, therefore, its integration proved difficult. It has been previously shown that resolution consider- ably increases in the inverse mode [30]. Hence, the technique was applied in order to better differentiate between the OTA peak and its busy surrounding.…”
Section: The Inverse Modementioning
confidence: 99%
See 1 more Smart Citation
“…Many effective techniques have been used to overcome this problem, which were classified into noncomputer and computer methods. The first method can be performed by changing the experimental and instrumental conditions including electric field, gate pulse width, temperature, pressure, drift tube length, drift gas, buffer gas modifier, high‐resolution IMS, and inverse IMS …”
Section: Introductionmentioning
confidence: 99%